Influence of physical and chemical factors on the survival of pichia isolated from glucose syrup - Rubio, María Cristina (2009)
Yeasts belonging to the genus Pichia were isolated fr om glucose syrup samples. Yeasts were identified as P. anomala ( it is now Wickerhamomyces anomala) and P. guilliermondii. These strains did not metabolize the nutritive preservatives, potassium sorbate or sodium benzoate when these were used as the single carbon source. P. anomala grew in culture media containing up to 1200 mg/L of both preservatives. Critical temperature and time of exposure for its inactivation were 60 °C and 3 min, respectively. P. guilliermondii grew in media containing up to 1400 mg/L of both preservatives. Critical temperature and time for inactivation of this Pichia were 80 °C and 2 min. This strain was able to grow in a wide range of temperatures (5 to 30 °C), pH (2.5 to 5.5) and glucose concentrations (200 to 800 g/L). At 5 °C and 800 g/L glucose (osmotic pressure, 0.110 atm), P.guilliermndii gr ew poorly , with no cell death because of its ability to sporulate. We determined that P. guilliermondii is a potentially contaminating yeast able to develop in a variety of foods, especially those with low pH or with high sugar concentrations (glucose above 400g/L) such as refreshments, juices, syrups and confected fruits and it is resistant to both food preservatives and low temperatures (5°C).